3-x-9+15x=

Simple and best practice solution for 3-x-9+15x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-x-9+15x= equation:


Simplifying
3 + -1x + -9 + 15x = 0

Reorder the terms:
3 + -9 + -1x + 15x = 0

Combine like terms: 3 + -9 = -6
-6 + -1x + 15x = 0

Combine like terms: -1x + 15x = 14x
-6 + 14x = 0

Solving
-6 + 14x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 14x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 14x = 0 + 6
14x = 0 + 6

Combine like terms: 0 + 6 = 6
14x = 6

Divide each side by '14'.
x = 0.4285714286

Simplifying
x = 0.4285714286

See similar equations:

| 3x+(-2x)+x=3x+18 | | 3t+8=5t+8-2t | | 3(x-4)=-1.2 | | 100x-29=42671 | | 1/4x-1/8x=3-1/16x | | 60x=100 | | 7(a+2)=34.3 | | x*3=18 | | 0.25y-3.5=0.15y+1-0.8y | | 100x-29=100(426.71) | | -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 | | ax=5a | | n^3-n=7n^2-5 | | n^3-n=7n^2-5 | | 3x=b/a | | 17(3)= | | 7p=50.4 | | 8x+14=12x-22 | | 3(x+5)+4(x-3)-6x=4 | | 17m=170 | | (x)(x+8)=96 | | 120-4x=40 |

Equations solver categories